2007
DOI: 10.1016/j.seizure.2007.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy study of bilateral thalamus in juvenile myoclonic epilepsy

Abstract: In the previous studies, NAA values in patients with JME found that they were not statistically lower in thalami than control group. But, in our study, NAA value was found low as well. It has been known that NAA is a neuronal marker and hence it is a valuable metabolite in the neuron physiopathology. As a result, in the patients with JME we tried to support the theory that the underlying mechanism of the generalized seizures was the abnormal thalamocortical circuity, determining the thalamic neuronal dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
(43 reference statements)
5
29
1
1
Order By: Relevance
“…23,24 Thalamocortical dysfunction is considered to be the major mechanism of JME. MRS studies have reported reduced NAA in the frontal lobe and thalamus, 9,10 consistent with the results reported in the present article. The involvement of these regions may be related to the pathomechanisms of seizure generation in this form of generalized epilepsy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…23,24 Thalamocortical dysfunction is considered to be the major mechanism of JME. MRS studies have reported reduced NAA in the frontal lobe and thalamus, 9,10 consistent with the results reported in the present article. The involvement of these regions may be related to the pathomechanisms of seizure generation in this form of generalized epilepsy.…”
Section: Discussionsupporting
confidence: 92%
“…The spatial distribution of FA reduction in this study reflects a disruption to the architecture of the anterior and ventral thalamic circuits, which are regions that have strong reciprocal projections with the prefrontal cortex. 27 Disruption to these projections, as suggested by the results presented here and in previous MRS studies, [8][9][10]28 may explain frontal lobe dysfunction in patients with JME, which is frequently reported. [29][30][31][32][33][34] In particular, it has been shown that patients with JME scored significantly below age-, education-, and gendermatched controls on neuropsychological measures of attention, immediate verbal memory, mental flexibility, control of inhibition, working memory, processing speed, and verbal fluency.…”
Section: Discussionsupporting
confidence: 68%
“…However, glutamine and glutamate are not easily quantifiable at field strengths below 4 Tesla when their overlapping peaks start to separate and GABA measurement requires additional editing. In contrast, the neuronal marker N ‐acetyl aspartate‐glutamate (NAA) is quantifiable even at lower field strengths, and reduced NAA was observed in brain structures that are involved in epilepsy . Only few studies measured in vivo concentrations of GABA or glutamate and glutamine separately (Glx as sum of both, Glx) in patients with JME .…”
mentioning
confidence: 99%
“…Recent advances in quantitative neuroimaging enable detailed investigation of the brain in vivo. A few studies in single voxel magnetic resonance spectroscopy (MRS) or magnetic resonance spectroscopic imaging (MRSI) have provided evidence of both cortical and deep gray matter (GM) abnormalities, particularly in frontal lobe and thalamus, in IGE patients (Savic et al., 2000; Bernasconi et al., 2003; Mory et al., 2003; Savic et al., 2004; Helms et al., 2006; Haki et al., 2007; Lin et al., 2009; Doelken et al., 2010). However, findings in IGE using MRI volumetry and voxel‐based morphometry (VBM) methods on T 1 ‐weighted images have been inconsistent.…”
mentioning
confidence: 99%